Lymphocyte transformation response to pokeweed mitogen as a predictive marker for development of AIDS and AIDS related symptoms in homosexual men with HIV antibodies. Issue 6593 (1st August 1987) - Hofmann, B; Lindhardt, B O; Gerstoft, J; Petersen, C S; Platz, P; Ryder, L P; Odum, N; Dickmeiss, E; Nielsen, P B; Ullman, S
Abstract : To identify factors that may predict the development of the acquired immune deficiency syndrome (AIDS) or AIDS related symptoms various immunological measurements were studied in a group of homosexual men attending screening clinics for AIDS in Copenhagen. Fifty seven men whose ratio of T helper lymphocytes to T suppressor lymphocytes (CD4:CD8 ratio) was less than 1.0 before the study began were included. Forty two were positive for antibody to the human immunodeficiency virus (HIV), of whom 38 were reinvestigated after a median observation period of 10 months. Among the seropositive men the transformation responses to pokeweed mitogen and cytomegalovirus and the absolute count of CD4 positive lymphocytes were the most common abnormal values. In particular, a low relative response to pokeweed mitogen on initial investigation correlated with a worsened clinical condition on reinvestigation. The risk of a worsened clinical condition was 55 times higher in seropositive men whose responses to pokeweed mitogen were low than in other seropositive men. The corresponding relative risks for low transformation responses to cytomegalovirus and for a decreased absolute count of CD4 positive lymphocytes were 18 and six. The relative response to pokeweed mitogen is therefore a very sensitive short term predictive marker of the clinical condition of seropositive patients who have a CD4:CD8 ratio of less than 1.0.